Degradable gold core–mesoporous organosilica shell nanoparticles for two-photon imaging and gemcitabine monophosphate delivery. Issue 4 (27th September 2017) - Rahmani, Saher; Chaix, Arnaud; Aggad, Dina; Hoang, Phuong; Moosa, Basem; Garcia, Marcel; Gary-Bobo, Magali; Charnay, Clarence; AlMalik, Abdulaziz; Durand, Jean-Olivier; Khashab, Niveen M.
Abstract : The synthesis of degradable gold core–mesoporous organosilica shell nanoparticles is described. Abstract : The synthesis of degradable gold core–mesoporous organosilica shell nanoparticles is described. The nanoparticles were very efficient for two-photon luminescence imaging of cancer cells and for in vitro gemcitabine monophosphate delivery, allowing promising theranostic applications in the nanomedicine field.